The influence of green human resource management practices on organizational citizenship behavior for the environment - Kuganya, Nagendran (2022)
Environmental challenges like ozone depletion, climate change, illegal logging, loss of species in a specific habitat, and ecosystem devastation are serious problems affecting countries worldwide, including Malaysia. As a result, environmental stakeholders expect the organisation to make positive development in environmental practices and establish reasonable environmental responsibility standards. Organizational Citizenship Behavior for the Environment (OCBE), whether voluntary or involuntary, is widely seen as an essential component for greening the corporate. Green Human Resource Management (GHRM) strategies are projected to influence OCBE among Malaysian manufacturing employees. The objective of this study is to determine if GHRM practices influence OCBE by evaluating the relationship between the variables. The influence of three (3) dimensions of green human resource management practices, namely green recruitment and selection, green training and development, and green compensation and reward on OCBE among employees at Taiping, Perak manufacturing companies that practice GHRM. A total of 245 employees took part in the research. The research hypotheses were tested using regression analysis. The results showed that green recruitment and selection had no significant relationship with OCBE. It's most likely due to a lack of environmentally friendly methods implementation and a lack of understanding of the necessity of environmental protection. It is suggested that research and business practitioners review the current policy and apply the laws and regulations more tightly to all industries and employees. This could lead to an increase in pro-environmental behaviour at work. However, green training and development, as well as green compensation and reward, were proven to have a positive relationship with OCBE. The findings of this research had both theoretical and practical implications. The findings, which were evaluated using the Statistical Package for the Social Sciences (SPSS) Version 26, show that OCBE and GHRM have a positive relationship